1992
DOI: 10.1021/jm00082a018
|View full text |Cite
|
Sign up to set email alerts
|

Benzazepinone calcium channel blockers. 2. Structure activity and drug metabolism studies leading to potent antihypertensive agents. Comparison with benzothiazepinones

Abstract: As part of a program to discover potent antihypertensive analogues of diltiazem (3a), we prepared 1-benzazepin-2-ones (4). Benzazepinones competitively displace radiolabeled diltiazem, and show the same absolute stereochemical preferences at the calcium channel receptor protein. Derivatives of 4 containing a trifluoromethyl substituent in the fused aromatic ring show potent and long-acting antihypertensive activity. Studies of the metabolism of 4 lead to the metabolically stable antihypertensive calcium channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 1 publication
1
30
0
1
Order By: Relevance
“…Indeed, the diltiazem scaffold is amenable to medicinal chemistry, as shown previously (Floyd et al, 1992). The divergence between GHSR1a activity and L-type Ca 2ϩ channel binding activity (Schoemaker et al, 1987) observed in the structural analogs tested here demonstrates the potential for developing potent GHSR1a agonists lacking Ltype Ca 2ϩ channel blocking activity from the diltiazem scaffold.…”
supporting
confidence: 55%
“…Indeed, the diltiazem scaffold is amenable to medicinal chemistry, as shown previously (Floyd et al, 1992). The divergence between GHSR1a activity and L-type Ca 2ϩ channel binding activity (Schoemaker et al, 1987) observed in the structural analogs tested here demonstrates the potential for developing potent GHSR1a agonists lacking Ltype Ca 2ϩ channel blocking activity from the diltiazem scaffold.…”
supporting
confidence: 55%
“…Random Docking-For the ligand-docking computational experiments we have chosen one of the most potent BTZ derivatives, SQ32910 (14,18). Random docking of the ligand in the open channel was performed using the multi-MCM method as described previously (29,32).…”
Section: Resultsmentioning
confidence: 99%
“…The ligand-Ca 2ϩ coordination can explain the above SAR peculiarity as well as the potentiation of diltiazem binding by Ca 2ϩ (7). Replacements of the ammonium group by hydrophilic groups significantly decreased the BTZ potency, suggesting a nucleophilic site in the receptor (14). Two nucleophilic sites are Experimentally found BTZ-sensing residues (1, 2, and 7) are bold.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely used in therapy, the compound has a relatively short duration of action. In the search for superior compounds, Floyd et al (21) substituted the benzazepinone ring structure for the benzothiazepinone of diltiazem. Metabolism studies on this class of compound showed that the principal routes of metabolism were similar to that for diltiazem with N-demethylation, conversion to an aldehyde, (pre-cursor of an acid), deacetylation and N-demethylation all occurring.…”
Section: Conjugation and Compound Structurementioning
confidence: 99%